The Right to Refuse AI (BioLaw Journal - Rivista di BioDiritto, 2026)
The progressive integration of artificial intelligence (AI) into professional and decision-making contexts raises unprecedented questions about the individual’s right to refuse such technologies. This contribution explores the legal recognition of a right to reject AI, based on three core motivations: environmental protection, the defense of human dignity in care settings, and the safeguarding of freedom of thought. Engaging with recent theoretical developments on a “right to AI”, the analysis argues that in a pluralistic and constitutionally grounded legal system, the systemic adoption of intelligent technologies must be counterbalanced by the recognition of a right to dissent, especially when rooted in ethical or professional concerns.
Keywords: artificial intelligence; right to AI; right to refuse; freedom of thought